Teori-Teori Belajar dan Implikasinya dalam Pembelajaran Pendidikan Agama Islam - Muhammad saman; Ani Cahyadi (Advances In Education Journal, 2026)
Learning theories play an important role in shaping effective Islamic Religious Education learning processes. However, Islamic Religious Education learning practices often emphasize cognitive aspects and neglect the integration of learning theories that support holistic student development. This study aims to examine learning theories and their implications for Islamic Religious Education learning. The research employs a qualitative descriptive approach using library research methods. Data were collected through the analysis of books, academic journals, and relevant scholarly works related to learning theories and Islamic education. The findings indicate that behavioristic, cognitive, constructivist, and humanistic learning theories have complementary roles in Islamic Religious Education learning. Behavioristic theory supports habituation of religious practices, cognitive theory strengthens understanding and reasoning, constructivist theory promotes contextual learning, and humanistic theory develops religious awareness and character. The study concludes that integrating learning theories contributes to meaningful, holistic, and value-based Islamic Religious Education aligned with the goals of Islamic education.